The Implementation of Khyar in Online Purchase and in Increasing Costumers Satisfaction - kamir, Kamiruddin Amhy; Hamzah, Aksi; Nikmah Marzuki, Sitti; Kamaruddin (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims at encouraging students to implement khyar in online transactions and creating its’ application model in order to obtain costumers satisfaction. The research was initiated due to the development of common online purchase and transactions whose applications are different from that of khyar. This can also potentially cause the business to lose its’ element of spiritual blessings and be susceptible to fraud and loss on the side of the costumers. The crucial issue found in the research is that what students learn at schools or campus in theories are not in line with what the application of kyar in real life. The nature of the research is descriptive and qualitative and its’ object is the implementation of khyar in online purchase and its’ data source is taken from students of the Faculty of Islamic Business and Economy who make online purchase and transactions. The instruments of research are observations, interviews and field records and data tabulation techniques used are editing, descriptions and interpretations. The result of the research shows that the conceptual implementation of the khyar is agreed upon by all of the students except for five of them. There are vendors who sold their products over someone else’s bargain and there are those who denied products return while according to Islam that practice should be allowed under the ruling of khyar.